2019
DOI: 10.3390/rs11121496
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining High-Resolution Seabed Topography and Surface Details by Co-Registration of Side-Scan Sonar and Multibeam Echo Sounder Images

Abstract: Side-scan sonar (SSS) is used for obtaining high-resolution seabed images, but with low position accuracy without using the Ultra Short Base Line (USBL) or Short Base Line (SBL). Multibeam echo sounder (MBES), which can simultaneously obtain high-accuracy seabed topography as well as seabed images with low resolution in deep water. Based on the complementarity of SSS and MBES data, this paper proposes a new method for acquiring high-resolution seabed topography and surface details that are difficult to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…As for the side-scan sonar, there are in general two types: (a) towed systems and (b) hull-mounted sonars [37]. Sonar emits a wide vertical (40-50 • ) and narrow horizontal beam (0.2-1 • ) [38] and receives seabed echoes at fixed time intervals to produce a high-resolution bottom imagery [39]. The returning echoes are displayed as one single line, where dark and light portions represent strong and weak echoes relative to the travel time.…”
Section: Mapping the Shipwreck-sitementioning
confidence: 99%
“…As for the side-scan sonar, there are in general two types: (a) towed systems and (b) hull-mounted sonars [37]. Sonar emits a wide vertical (40-50 • ) and narrow horizontal beam (0.2-1 • ) [38] and receives seabed echoes at fixed time intervals to produce a high-resolution bottom imagery [39]. The returning echoes are displayed as one single line, where dark and light portions represent strong and weak echoes relative to the travel time.…”
Section: Mapping the Shipwreck-sitementioning
confidence: 99%
“…Between 1984 and 2018, the maximum lake area is 541.27 km 2 in 1998; the median lake area is 468.90 km 2 in 1991; and the minimum lake area is 309.84 km 2 in 2016 (illustrated in Figure 7). Then, water volumes were calculated via the method by combining water areas and water levels of Lake Mead using Equation (7). To make our estimated lake water volumes and in situ data comparable, their systematic offset was removed.…”
Section: Lake Water Volume Estimation and Validationmentioning
confidence: 99%
“…Unfortunately, in situ data of water levels/volumes of lakes across the globe are very limited, especially for developing countries and some remote areas. Previous studies also reported that the lake water level and volume can be obtained by the bathymetric data derived from various sensors [6], e.g., ship-borne singlebeam or multibeam echo sounders, and airborne bathymetric lidars (Light detection and ranging) [7][8][9]. However, the high cost of those accurate bathymetric data limits the use of this approach at a global scale [10].…”
Section: Introductionmentioning
confidence: 99%
“…The image matching of consecutive frames is a critical step in the mosaic process, which can be broadly categorized into feature-based matching and pixel intensity-based matching [17]. The feature-based methods such as Harris [18], SIFT or SURF [19] assume that distinct feature points in both the source image and the examined image can be reliably detected and elaborated by image descriptors. Given enough potent matches of feature points, it is possible to estimate the matching parameters between two images.…”
Section: Related Workmentioning
confidence: 99%